2004
DOI: 10.1136/adc.2002.009738
|View full text |Cite
|
Sign up to set email alerts
|

Maternal depression and low maternal intelligence as risk factors for malnutrition in children: a community based case-control study from South India

Abstract: Aims: To determine whether current and postpartum maternal depression and low maternal intelligence are risk factors for malnutrition in children. Methods: In rural South India 72 children with malnutrition were identified from a central register; 72 controls were matched for age, gender, and residence. Results: Major depression in the postpartum period (OR 5.0, 95% CI 1.0 to 24.0), current major depression (OR 3.2, 95% CI 1.1 to 9.5), and low maternal intelligence (OR 3.8, 95% CI 1.3 to 11.1) were associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
93
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(105 citation statements)
references
References 11 publications
8
93
2
2
Order By: Relevance
“…23,24,[29][30][31][32][33][34][36][37][38][39] Meta-analysis of these studies showed that the relationship between maternal depression and underweight (OR: 1.5; 95% CI: 1.2-1.8) remained similar to that in the meta-analysis of all studies and the heterogeneity persisted (Q = 37.83, P = 0.001). When the meta-analysis was restricted to the nine studies that used measures of depression or depressive symptoms, 24,25,29,31,[33][34][35]38,39 the relationship between maternal depression and underweight strengthened and remained statistically significant (OR: 1.7; 95% CI: 1.2-2.4), and the findings remained heterogeneous (Q = 18.70; P = 0.017). Finally, when the meta-analysis was restricted to the four longitudinal cohort studies, 31,33,35,38 the relationship strengthened further (OR: 2.2; 95% CI: 1.5-3.2) and high homogeneity was noted (Q: 2.47; P = 0.48).…”
Section: Systematic Reviews Pamela J Surkan Et Almentioning
confidence: 70%
See 1 more Smart Citation
“…23,24,[29][30][31][32][33][34][36][37][38][39] Meta-analysis of these studies showed that the relationship between maternal depression and underweight (OR: 1.5; 95% CI: 1.2-1.8) remained similar to that in the meta-analysis of all studies and the heterogeneity persisted (Q = 37.83, P = 0.001). When the meta-analysis was restricted to the nine studies that used measures of depression or depressive symptoms, 24,25,29,31,[33][34][35]38,39 the relationship between maternal depression and underweight strengthened and remained statistically significant (OR: 1.7; 95% CI: 1.2-2.4), and the findings remained heterogeneous (Q = 18.70; P = 0.017). Finally, when the meta-analysis was restricted to the four longitudinal cohort studies, 31,33,35,38 the relationship strengthened further (OR: 2.2; 95% CI: 1.5-3.2) and high homogeneity was noted (Q: 2.47; P = 0.48).…”
Section: Systematic Reviews Pamela J Surkan Et Almentioning
confidence: 70%
“…1), [23][24][25][29][30][31][32][33][34][35][36][37][38][39] covering a combined study population of 13 923 mother and child pairs. The pooled data showed a moderate, statistically significant relationship between maternal depression and underweight (OR: 1.5; 95% confidence interval, CI: 1.2-1.8).…”
Section: Underweight Meta-analysismentioning
confidence: 99%
“…Indeed, a growing body of evidence suggests that exposure to maternal depressive symptoms may negatively impact young children's growth and health (19,20) . However, while some research has linked maternal depressive symptoms to an increased likelihood of being underweight among young children in certain developing countries or ethnic groups in the USA (21,22) , other research in Europe, Africa, and North and South America has found no associations (19,23) . Similarly, the limited research on maternal depressive symptoms and child height and weight has produced mixed results, with some studies finding positive associations between exposure to maternal depressive symptoms during infancy and their children's subsequent probability of being overweight (14,24) and others finding no association with weight (25,26) or height outcomes (27) .…”
mentioning
confidence: 99%
“…Different studies have observed a relationship between weight faltering in the first two years with both elevated maternal EPDS and higher rates of diagnosed depression in mothers (O'Brien et al 2004). Studies in developing countries have consistently found a correlation between maternal depression and weight faltering, suggestive of maternal depression possibly being a key factor of underprivileged populations (Anoop et al 2004;Patel et al 2004).…”
Section: Introductionmentioning
confidence: 99%